Pengujian Efektifitas Mekanisme Corporate Governance terhadap Kualitas Pengungkapan: Studi pada Perusahaan Terkonsentrasi di Indonesia - Ariningrum, Hardini; Gumanti, Miswan; Kasmi, Kasmi; Afif, Muhammad Faris (Universitas Pamulang, 2025)
This study aims to examine the Corporate Governance (CG) mechanism or corporate governance on the quality of disclosure on the characteristics of companies with highly concentrated ownership, with low investor protection.CG is proxied by several Corporate Governance mechanisms and disclosure quality as measured by the Disclosure Index. The sample of this study is a concentrated manufacturing company that has a majority shareholder. The analysis method uses the Multiple Regression Analysis (MRA) statistical test, with the results of the study proving that the Corporate Governance mechanism, namely the size of the board of directors, the size of the board of commissioners, independent commissioners, and institutional ownership are significant and positive on the quality of disclosure. However, evidence shows that ownership concentration has a negative effect on the quality of disclosure under highly concentrated ownership. This evidence suggests that the effectiveness of CG mechanisms needs to be part of regulations to protect investor rights and for standard setters and regulators to improve the quality of disclosure as an important way to reduce agency conflicts and increase accountability and transparency.